Quality practices as a moderator in technology transfer performance - Muhamad Noor, Sarina; Yusoff, Rushami Zien; Hashim, Fariza (Canadian Center of Science and Education, 2009)
Absorptive capacity is one of the factors that determines the success of technology transfer. It improves one’s ability to assess the current and future needs of firms and leads them to make better choices. At the same time, quality movement in firms also has a similar vision; to make firms move forward in a competitive way. The objective of this paper is twofold. First, was to determine the association between absorptive capacity and technology transfer dimensions. Secondly, this study was conducted to determine the moderating role of firms’ quality practices in the relationship between firms’ absorptive capacity and technology transfer performance. Data was collected from Malaysian firms through mailed questionnaires. With a response rate of 32%, data was analyzed using multiple hierarchical regression and Chi Square method. The results showed quality process interacts significantly with knowledge diversification and transformative capacity during the integration stage. Moreover, the addition of a moderating variable increases the prediction of technology transfer performances. The result suggests firms’investment in quality practices improves the process of transferred technology.